Employee Performance Influenced by Leadership and Work Discipline - Diana Pramudya Wardhani; Nenden Annisa; Deria Dwi Elfarina (Social Science Studies, 2023)
Human Resources (HR) is one of the important factors of an organization because it acts as a mover, thinker, and planner to achieve organizational goals. Therefore, an organization must be able to build and improve the performance of its employees. The efforts to improve employee performance include paying attention to leadership, work discipline, and motivation. The aims of this study were (1) to examine the influence of leadership on employee performance, (2) to examine the effect of work discipline on employee performance. The population in this study were all employees of PT. New Cakti Purworejo and obtained a sample of 70 respondents. The data collection instrument used a questionnaire with a Likert scale, each of which had been tested and met the validity and reliability requirements. Data analysis used multiple linear regression using SPSS 22.0 for Windows software tools. The results showed that (1) leadership has a positive effect on employee performance, (2) work discipline has a positive effect on employee performance